Factors that increase the effectiveness of regional innovation systems - A. Solomatin (Вестник университета)
This paper examines the factors increasing the efficiency of regional innovation systems as the basis of the strategy of economic growth in the region . The reasons for reducing the effectiveness of public investment in research and development activities . It was found that , the higher the efficiency of national and regional investment programs associated with public investment programs in order to attract private capital through public-private partnerships.